ANALISIS STRATEGI PEMASARAN TABUNGAN SIKOCI SYARIAH MENGGUNAKAN AKAD MUDHARABAH DALAM MENINGKATKAN JUMLAH NASABAH (STUDI KASUS BANK NAGARI CABANG SYARIAH PAYAKUMBUH) - Gita Aprilia; Rahmi Rahmi (CV. Adiba Aisha Amira, 2025)
To put it simply, a bank is a type of financial institution that takes deposits of people's savings and then lends those funds out to them in various ways to raise everyone's level of living. Sikoci Syariah Savings, a superior product owned by Bank Nagari, is one of the many popular funding products in the community. It is based on the wadiah and mudharabah contract principles and offers annual increases to its customers. Qualitative descriptive research is what this study is all about. Interviews were held at the PT. Bank Nagari Sharia Branch Payakumbuh with customers, the marketing department's Deputy Manager, and other bank staff. Methods such as observation, interviews, and documentation are employed to gather data. The Marketing Mix is the instrument used for analyzing all of this data. One outcome of this research is the marketing approach used by the Payakumbuh branch of Bank Nagari Syariah to attract more consumers. This approach makes use of the marketing mix, which includes the following elements: product, price, place, promotion, people, physical evidence, process, public relations, and power strategy. (2) Efforts to address marketing strategy roadblocks in expanding the sikoci syariah mudharaba savings product's client base, including re-evaluating the target market, fostering customer contact, tailoring product development to customer needs, and providing exclusive deals.